Deep Sea Port and the National Development: Perspective of Bangladesh - Anis Mohammad Tareq; Md Akramuzzaman Shaikh; Sukanta Sen; Wang Xuefeng (International Journal of Engineering and Management Research, 2020)
The deep sea port development as an economic infrastructure influences positively on the growth of a country. The economic history of Britain, Netherlands, and Singapore, known as the maritime powers in the world, undoubtedly proves the important role of ports played in the development of their economies. Establishment of a deep-sea port has become strategically very critical for Bangladesh considering its potential impact on the development and economic growth of the country.Port economics and macroeconomics are closely related.So changes in port traffic or operation and port organization has a significant impact on national economy especially on the hinterland. This study, therefore, has focused on the importance of deep seaport in the national development of Bangladesh. Moreover, the paper gives an overview of a deep seaport and national development in respect of Bangladesh.The study also indicates the effect of a deep seaport on national development. At the end, this study states some recommendations for the establishment of the deep sea port.Those Includes-Studies on the selection of strategic location, details investigation of hinterland connectivity, the decision on investment and proper planning etc.